Planning and Implementation of Social Studies Learning at SDN Anjir Serapat Muara 1.2 - Risna Putra Pradana; Syaharuddin Syaharuddin; Mutiani Mutiani; Muhammad Rezky Noor Handy; M. Ridha Ilhami (Universitas Lambung Mangkurat, 2024)
This article discusses how teachers at SDN Anjir Serapat Muara 1.2 carry out the planning and implementation of social studies learning. This research was carried out to describe activities related to planning and also implementing social studies learning in SDN Anjir Serapat 1.2. SDN Anjir Serapat Muara 1.2 became the place for this research. The method used in this study is a descriptive method of observing, interviewing, and documenting to obtain data. The data analysis used is data reduction, data presentation, and verification as a conclusion. Testing the validity of the data in this study was carried out by triangulating sources and techniques, extending observations, and using reference materials. The results of the study showed that social studies learning plans were made by teachers, namely lesson plans, which in the manufacturing process were guided by the 2013 syllabus and curriculum with one wide lesson plan format. Then the components contained in the lesson plans that the teacher contains such as themes/materials, school identity, time allocation, KI and KD, models, and assessments which are then further developed in the preliminary, core, and closing activities. Furthermore, related to the implementation of social studies learning, the implementation of social studies learning at SDN Anjir Serapat Muara 1.2 is carried out with three stages of activity, namely starting with the preliminary activity stage, then continuing with the core activities, and ending with closing activities. The teacher performs his role as a teacher, guide, facilitator, and evaluator.